Entrepreneurial Competencies of The Household Industries of Local Foods in Bogor District West Java - Faizal Maad; Linar Humaira (Indonesian Journal of Social Research (IJSR), 2019)
The purpose of the study is to analyze individual characteristics of the entrepreneurs from household industries of local foods, the government policy support, entrepreneurial competence level as well as the determinant factors of the entrepreneurial competence of household industries of local foods in Bogor district’s, West Java . The study uses survey methods using descriptive statistical analysis and inference statistics to 231 home-based local food manufacturing industries in 14 sub-districts and 20 villages in Bogor. The results of this study indicate that the entrepreneurial competencies of household industries of local foods in Bogor district’s is low. The determinant factors of the entrepreneurial competence consist of formal education, motivation, and cosmopolitan mindset of the household industry entrepreneurs of local foods as well as the government policy support for the development of household industries of local foods. To increase the entrepreneurial competence of the entrepreneurs from household industries of local food, the entrepreneurs need to increase their non-formal education, motivation, and cosmopolitan mindset as well as the goverment policy support